A mulher e o cinema: representação feminina no mercado cinematográfico brasileiro - Thaís Botrel Reis (2017)
This dissertation aims at a study on the female representation in Brazilian films made in this century, starting from a problematization of how this representation occurs in dominant cinema. Traditionally in films, women appear as submissive and/or objectified characters. It has changed, though slowly, especially under the influence of the feminist movement, which has raised and still raises questions about the socially constituted and accepted phallocentric view; power relations imbued with misogyny and machism; the patriarchal definitions that the public space suits men and the private suits women better; and it has also showed the importance of topics such as prostitution, marriage, motherhood, the division of gender roles, women's rights, etc. These questions have reflected on the film industry, concerning the increase in female participation as well as the themes in films. In addition, the representation of women has also showed itself as a fundamental matter to film debates. Authors such as Laura Mulvey, E. Ann Kaplan and Teresa de Lauretis relate this issue to a possible differentiation between socially constructed points of view, transmitted through the directors aesthetic choices. Taking this into consideration and also recognizing the importance of feminist advances towards deconstructing the traditional male gaze perpetuated in dominant cinema, this dissertation purpose is to explore Brazilian films recently made, mainly the ones directed by women, fomenting the problematization of female representation on cinema through ideas formerly proposed by the mentioned authors.